Pengaruh Gaya Kepemimpinan Dan Komitmen Organisasi Terhadap Disiplin Kerja Dengan Kepuasan Kerja Sebagai Variabel Intervening (Pada Karyawan PT. PLN (Persero) Area Surakarta) - Setiawan, Edi, Drs. M. Farid Wajdi, M.M., Ph.D, Drs. Ahmad Mardalis, MBA (2015)
The aims of this study is to analyze the factors - factors that can affect the employee job satisfaction and work discipline in the PT. PLN (Persero) AREA Surakarta. Research model that will be used in this research is a tiered structure model and to test the hypothesis used analytical techniques SEM (Structural Equation Modeling) which is run by the application SmartPLS 2.0.M3. Based on the results of the analysis shows that the style of leadership is not a positive influence on work discipline, organizational commitment is a positive influence on work discipline, leadership style has a positive effect on job satisfaction, organizational commitment is a positive influence on job satisfaction, job satisfaction and positive effect on labor discipline. Model of the influence of leadership style, organizational commitment and job satisfaction on work discipline produces the R - square value is to show good models. It means that the variability of labor discipline constructs can be explained by the variability of the construct of leadership style, organizational commitment and job satisfaction. The model of the influence of leadership style and organizational commitment on job satisfaction produces the R-square value indicates a moderate models, it means that the construct of job satisfaction variability can be explained by the variability of the construct of leadership style, and organizational commitment